Grasses of Certain Areas in Jhunjhunu District, Rajasthan - Joshi, M. C.; Sarma, C. B. S. R. (Indian Forester, 1966)
51 grasses-22 belonging to the subfamily Panicoideae and 29 to the subfamily Pooideae are reported from certain areas of Jhunjhunu district, Rajasthan. Occurring most frequent are those of tribe Eragrosteae. The above data are compared with those of other investigated areas of the state. It is found that tribe Paniceae, in general, is dominant in the state. The grasses further categorized into habitat c1asses.